UTILIZATION OF PADLET IN SECOND LANGUAGE TEACHING: PRACTICES, CHALLENGES, AND OPPORTUNITIES - Villarama, Joseph Agbuya; Pilien, Ramil Vicente; Villamar, Czerina Igcasan (LLT Journal: A Journal on Language and Language Teaching, 2025)
The landscape of second language classrooms (SLCs) adapts to innovative language teaching strategies to empower language learners through various technology applications such as Padlet, which offers a dynamic and enhanced learners’ academic experience. This phenomenological qualitative research explored the utilization of Padlet in second language classroom teaching, along with the encountered problems of language learners in using Padlet, and its technological potential in second language teaching and learning. The data were analyzed thematically after a series of scheduled semi-structured face-to-face interviews with 210 learner-participants selected through a purposive sampling technique, while guided by a validated 15 self-developed interview guide questions. The findings highlight the Padlet as an efficient, multifunctional, and novel pedagogical tool fostering dynamic and inclusive language engagement and versatile language learning interactions, despite its restriction issues due to their limited technology exposure. With Padlet’s promising results, this study substantiates pedagogical evidence on Padlet integration in second language classroom teaching; hence, ensuring a more effective and efficient technology utilization, thereby handing more positive implications to ESL teachers and learners.